A facile method to in situ fabricate three dimensional gold nanoparticle micropatterns in a cell-resistant hydrogel. Issue 2 (20th January 2016) - Yao, Ming-Hao; Yang, Jie; Zhao, Dong-Hui; Xia, Rui-Xue; Jin, Rui-Mei; Zhao, Yuan-Di; Liu, Bo
Abstract : A facile method for in situ fabrication of three-dimensional gold nanoparticles micropatterns throughout a polyethylene glycol hydrogel substrate has been developed by combining photochemical synthesis of gold nanoparticles with photolithography technology. Abstract : A facile method for in situ fabrication of three-dimensional gold nanoparticle micropatterns in a cell-resistant polyethylene glycol hydrogel has been developed by combining photochemical synthesis of gold nanoparticles with photolithography technology. The gold nanoparticle micropatterns were further bio-modified with cell integrated polypeptide NcysBRGD based on a gold–thiol bond to improve cell behaviors. Primary cell tests showed that NcysBRGD can enhance cell adhesion very well on the surface of gold nanoparticle micropatterns.